Influence leadership style and work environment on conflict and employee performance - Burhan, Hasdiana; Mardiana, Ria; Aswan, Andi (Scientia integritas Utama, 2022)
This study aims to analyze leadership style that has an indirect influence on employee performance through conflicts that occur in the Regional Financial and Asset Agencies of Maros Regency and to analyze the work environment that has an indirect influence on employee performance through conflicts that occur in Regional Financial and Asset Agencies Mars County. This study uses a quantitative approach. The data used is primary data. A sample of 60 respondents. The respondent is a permanent employee/state civil apparatus of the Maros Regency Regional Finance and Assets Agency. Data collection was carried out through a survey using a questionnaire distributed to respondents. Data were analyzed using multiple regression analysis and path analysis using the statistical package for the social sciences (SPSS) version 24. The results showed that leadership style and work environment have a direct influence on employee performance through conflict that occurred in the Maros Regency Regional Financial and Asset Agency, and there was an indirect influence on employee performance through conflicts that occurred in the Maros Regency Regional Financial and Asset Agency. This shows that when the leadership style and work environment are high, the employee's performance will increase and vice versa. The results of the study show that leadership style and work environment have a direct influence on employee performance through conflicts that occur in the Maros Regency Regional Finance and Asset Agency, and there is an indirect influence on employee performance through conflicts that occur in the Maros Regency Regional Financial and Asset Agency . This shows that when the leadership style and work environment are high, the employee's performance will increase and vice versa. The results of the study show that leadership style and work environment have a direct influence on employee performance through conflicts that occur in the Maros Regency Regional Finance and Asset Agency, and there is an indirect influence on employee performance through conflicts that occur in the Maros Regency Regional Financial and Asset Agency . This shows that when the leadership style and work environment are high, the employee's performance will increase and vice versa.